Changes in mammographic density over time and the risk of breast cancer: An observational cohort study. (August 2019) - Román, Marta; Sala, Maria; Baré, Marisa; Posso, Margarita; Vidal, Carmen; Louro, Javier; Sánchez, Mar; Peñalva, Lupe; Castells, Xavier
Abstract: Background: The effect of changes in mammographic density over time on the risk of breast cancer remains inconclusive. Methods: We used information from four centres of the Breast Cancer Screening Program in Spain in the period 1996–2015. We analysed individual level data from 117, 388 women first screened age 50–54, with at least two screening examinations. Breast density was determined using the BI-RADS classification (A to D in increasing order) at earliest and latest screening examination. Adjusted Poisson regression models were used to estimate the relative risk (RR) and 95% confidence intervals (95%CI) of the association between changes in mammographic density and breast cancer risk over time. Results: During an average 5.8 years of follow-up, 1592 (1.36%) women had a breast cancer diagnosis. An increase in density category increased breast cancer risk, and a decrease in density decreased the risk, compared with women who remained in the same BI-RADS category. Women whose density category increased from B to C or B to D had a RR of 1.55 (95%CI = 1.24–1.94) and 2.32 (95%CI = 1.48–3.63), respectively. The RR for women whose density increased from C to D was 1.51 (95%CI = 1.03–2.22). Changes in BI-RADS density were similarly associated with the risk for invasive cancer than for ductal carcinoma in situ. Conclusions: Although a modest proportion of women changed BI-RADS density category, mammographic density changes modulated the risk of breast cancer and identified women at a differential risk. Using two longitudinal measures of BI-RADS density could help target women for risk-based screening strategies. Highlights: A modest proportion of women changed breast density category over time. Mammographic density changes had an impact on the risk of subsequent breast cancer. An increase in density category over time could double breast cancer risk. A decrease in density category over time reduced breast cancer risk by up to 50%. Two longitudinal measures of breast density can help target women at increased risk.